Uma recontextualização do pensamento freireano nas sociedades complexas: a autonomia como um princípio educativo democrático - Marques, Franciele Fátima (2016)
This research, supported in Paulo Freire's work reference, searching reflection on the imagery of autonomy and its reconfiguration in specifically educational field, assess the possibilities and effectiveness of recontextualising a pedagogy of autonomy, linked to the democratic principles on which the citizenship of the subjects. Such individual strand of imagery of autonomy is present in current discussions about the educational process and has, over the years, being in intellectual topic of concern and responsible institutions that are involved with education. Autonomy was formed from the Modernity in a central educational principle and of paramount importance to the development of the field of education there on. Currently, the issue of autonomy has received numerous criticism and problematizations about the approach of such a concept within a neoliberal perspective and postmodern, which requires a resumption of sense in a context that is complex, multicultural, diverse, plural. The increasing complexity of society and the sophistication of the mechanisms of control and manipulation of individuals have grown in intensity, which has hindered not only the free action of the same, as resizes the understanding of autonomy and freedom that it is up to each individual exercise. This research aims, therefore, the search for fecundity analysis of reflections of Freire and their pedagogical proposals in the context of new forms of social reproduction, economic and political. The main question guiding this thesis is about Freire's critique of the potential for current education and as a recontextualising its concern about the autonomy of the subjects can contribute significantly in the development of emancipation, the transformation of autonomy "of jure "in autonomy" in fact ". Therefore, in addition to performing a hermeneutical and critical exercise on Freire's pedagogy, carried out an approach to contemporary conceptions of emancipatory education, specifically the theory of empowerment and renewed liberating education. The hypothesis is that the pedagogical approach of the theory of liberation of Freire, linked to the construction of the autonomy process, can still bring very effective contributions in the context of a globalized society and multicultural development. The findings point to the relevance of Freire's conception of education for and autonomy as a prerequisite for the development of democratic society. In this process we highlight the Freirian categories dialogue, context, participation and multicultural collaborative practice. Autonomy, and democratic may converge in interconnected principles, so the other a need for effective practice. The democratic educational practice therefore requires a radical democracy based on participation as "empowerment" in decision-making on the part of the school and the participating subjects.